2017
DOI: 10.21276/apalm.1456
|View full text |Cite
|
Sign up to set email alerts
|

Corynebacteriumamycolatum causing breast abscess: An infecting Diphtheroid with a difference

Abstract: Corynebacterium amycolatum has been rarely reported from cases of breast abscess/mastitis. We describe a case of Corynebacterium amycolatum causing breast abscess with fistula formation. The identification of the organism was done by MALDI-TOF (Matrix assisted Laser Desorption Ionization Time of Flight) Vitek MS (Mass spectrometry) [Biomerieux, France] and Vitek-2 (Biomerieux, France). The clinical significance of the organism was ascertained in view of presence of many polymorphonuclear cells along with Gram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…We have earlier reported a case of breast abscess with fistula formation due to C.amycolatum at our institute. [11] We believe that in the earlier years we would have isolated Corynebacteria from breast specimens but it would have been considered as of doubtful significance because of non-definitive identification of the isolate. MALDITOF MS has thus played a vital role in understanding the significance of these species from breast pus/tissue specimens.…”
Section: Discussionmentioning
confidence: 98%
“…We have earlier reported a case of breast abscess with fistula formation due to C.amycolatum at our institute. [11] We believe that in the earlier years we would have isolated Corynebacteria from breast specimens but it would have been considered as of doubtful significance because of non-definitive identification of the isolate. MALDITOF MS has thus played a vital role in understanding the significance of these species from breast pus/tissue specimens.…”
Section: Discussionmentioning
confidence: 98%
“… 1 C. amycolatum is also a part of the skin flora, which has recently been reported to manifest various infections such as sepsis, device‐associated infections, endocarditis, empyema, and breast abscess. 1 , 4 In skin and soft tissue infections, C. amycolatum has been isolated from wound and surgical site infections. 5 , 6 Cases in immunocompromised conditions can be fatal.…”
Section: Discussionmentioning
confidence: 99%
“…Historically, Corynebacterium species have been underrated and ignored as a contaminant, as they are normal colonisers of the skin and generally show low virulence 1 . C. amycolatum is also a part of the skin flora, which has recently been reported to manifest various infections such as sepsis, device‐associated infections, endocarditis, empyema, and breast abscess 1,4 . In skin and soft tissue infections, C. amycolatum has been isolated from wound and surgical site infections 5,6 .…”
Section: Discussionmentioning
confidence: 99%
“…After doxycycline treatment, surgical intervention was not needed in this patient 22 . In a case report of breast abscess with fistula formation, Butta et al performed abscess drainage and fistula excision, continued the treatment with amoxicillin+clavulanic acid 1000mg (875/125mg) and doxycycline 200 mg for 7 days upon isolation of C. amycolatum in the tissue sample and reported that the patient responded fully to the treatment and recovered completely 23 . In our study to investigate the role of Corynebacterium strains in the etiology of granulomatous mastitis, tissue samples obtained from 41 patients were examined microscopically in terms of the number of microorganisms, staining characteristics and shapes of the existing microorganisms, and C. amycolatum was isolated from only 1 patient (2.4%).…”
Section: Discussionmentioning
confidence: 99%